The current role of radiotherapy and systemic therapy in the multidisciplinary treatment of cholangiocarcinoma - Soumarová, Renata; Gürlich, Robert; Hajer, Jan; Oliverius, Martin; Kubecová, Martina; Šejdová, Markéta; Liberko, Marián; Kološtová, Katarína (Casopis lekaru ceskych, 2019)
Cholangiocarcinoma is a cancer with very poor prognosis. The only potentially curative approach is surgical resection of tumor. However, the rate of local and distant recurrence after radical surgery is still high. Benefit of adjuvant therapy is not clearly defined, nevertheless patients at high risk of recurrence are indicated to chemotherapy or chemoradiotherapy. Locally advanced, unresectable disease can also be treated with chemotherapy alone, or with her combination with radiotherapy. Required radiation doses are relatively high, therefore it is necessary to use highly conformal radiation therapy. Treatment of metastatic disease is currently based on systemic therapy, combination of gemcitabine and cisplatin as standard of care. Benefit of targeted molecular therapy is not clear at present, but ongoing research in genetic profiling of tumor may help to improve current clinical practice. Patients with cholangiocarcinoma have to be discussed during multidisciplinary team meetings.
Keywords: dospělí; nádory žlučových cest; kombinovaná terapie; Adult; Bile Duct Neoplasms; Bile Ducts, Intrahepatic; cholangiokarcinom; lidé; radiotherapy adjuvant; nádory jater; targeted therapy; Liver Neoplasms; Cholangiocarcinoma; Combined Modality Therapy; chemoradioterapie; drug therapy; žlučové cesty intrahepatální; cholangiocarcinoma; Chemoradiotherapy; Humans